PEMBERDAYAAN UKM MAKANAN OLAHAN CARICA DI WONOSOBO, JAWA TENGAH - Eny Endah Pujiastuti; Humam Santosa Utomo; Suratna Suratna (Dharma: Jurnal Pengabdian Masyarakat, 2020)
The community service program is carried out at one of the SMEs in Wonosobo, Central Java, which produces and markets processed carica food products. The problems faced by SMEs are problems in the aspects of marketing, financial management and production. The purpose of community service is to improve the ability of SMEs to market products, manage company finances, increase the efficiency of the production process, and increase production capacity. The approach used in this community service is training and business assistance. The results felt by SMEs are the wider marketing of carica processed food products, structuring the company's financial system, efficiency in the production process, and increased production capacity.